(untitled) (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2025)
English language proficiency has become increasingly essential for non-English major students, both academically and professionally. This study investigates perception and motivation that drive non-English major students to learn English, the internal and external factors influencing their motivation, and the dominant factor motivating them to learn English. Using a cross-sectional survey design, data were collected through a structured questionnaire from undergraduate students at Program Studi Pendidikan Pancasila dan Kewarganegaraan, Universitas Negeri Makassar. The findings reveal that intrinsic motivation such as enjoyment, curiosity, and satisfaction in learning; emerged as the dominant factor, with 95% of students expressing enjoyment in learning English. Extrinsic factors like academic performance, career prospects, and social expectations also significantly influenced motivation. Moreover, students generally perceived themselves as competent in understanding classroom content but showed lower confidence in communicative skills. Many reported autonomous behaviours, such as setting goals and practicing independently. These results underscore the importance of fostering both internal interest and practical application through engaging and supportive instruction. Future research is recommended to explore motivational changes over time and the impact of interactive learning environments on communicative competence